The Correlation between Self-Confidence and Students' English Speaking Ability of SMP Negeri 2 Darul Imarah - Lianda, Nur Putri; Rizka, Budi; Muliawati, Ida (JETLi: Journal of English Teaching and Linguistics, 2023)
This study aims at identifying and describing the correlation between self-confidence and English-speaking skill. This research was conducted because the writer wanted to see how significant the influence between self-confidence and students’ speaking ability of SMPN 2 Darul Imarah Aceh Besar in class 8A. This study collected data in a different way in which this research prepared a test in form of self-introduction. Moreover, there has been no previous study that tested speaking in a way to build confidence at SMP Negeri 2 Darul Imarah Aceh Besar. The objective of this research is to know whether self-confidence has significantly influence on student’ English speaking ability of SMP Negeri 2 Darul Imarah. The writer used descriptive quantitative research method. This study involved 32 students and collecting data instruments of self-confidence questionnaire and speaking test. The results of the questionnaire determine the category of high confidence, five categories from very low to very high self-confidence. The second data is speaking test using self-introduction topic. The results of the speaking test determine students' speaking skills into five categories: poor, average, good, very good and excellent. After calculating the results of students' scores in speaking and self-confidence. The writer found that students have self-confidence in the high category. Moreover, the correlation coefficient (rxy) is 0.376. That means that the correlation is a low correlation. Based on the data above, the writer compared between rxy and rtable  rxy: r1= 0,376 > 0361,  the  writer concluded that H0 was rejected and H1 was accepted, which means there is a correlation between students' self-esteem and their speaking ability.